The Role of Green Marketing Innovation In Establishing Sustainable Tourism Based on Green Customers In Kesiman Kertalangu Tourism Village, Denpasar - Ekastuti, Ida Ayu Agung; Ardani, Wayan; Laksmana, Komang Agus Rudi Indra (Majalah Ilmiah Bijak, 2025)
The aim of this research was to analyze the direct effect of green marketing innovation and green customer on sustainable tourism,   and to explore the mediating role of   green customer on the effect of green marketing innovation on sustainable of tourism village in Kesiman Kertalangu, Denpasar, Bali. The population of this research was the tourists who visited Kesiman Kertalangu. There were 180 tourists being the respondents of this research. The data was analyzed using   SEM-PLS. This study revealed that Green marketing innovation and green customer had positive and significant effects on sustainable tourism. Furthermore, Green customer significantly mediated the effects of   green marketing innovation on sustainable tourism. Green marketing helps to create awareness and educate tourists about environmentally friendly tourism, while green customers drive demand and put pressure on the industry to adapt to sustainable practices. Collaboration between the two can create a more environmentally friendly tourism ecosystem and support the preservation of nature and culture in the future.